Experimental study on pool two-phase flow and droplet entrainment characteristics - Yu’ang Tan; Rulei Sun; Tan Ma; Puzhen Gao; Ruifeng Tian; Sichao Tan (Annals of Nuclear Energy, 2026)

Glucose mitigates propionate toxicity and enhances odd-chain fatty acid production in Schizochytrium sp.: mechanistic insights and rational fermentation design - Ziliang Deng; Zhao Zhang; Shuang Sun; Zihan Meng; Yaqi Xu; Min Gao; Jiayi Li; Ang Li; Weijia Li; Dongzhe Sun (Bioresource Technology, 2026)

Occurrence and behaviors of organophosphate esters in shallow grass-type lake ecosystems: The key role of aquatic plants - Mei Wang; Bing Wang; Yifan Zhang; Yihang Sun; Jingjing Zhao; Ang Zhao; Chao Wei (Water Research, 2026)

Dimensional reduction of hydrogen-bonding networks induced by hierarchical confinement to promote ultra-fast adsorption of hydrated ions to targeted sites - Meng Du; Zhiqiang Sun; Aiwen Wang; Ang Li; Jun Ma (Water Research, 2026)

Development of a global integrated environmental quality index for population health research - Wenjie Ruan; Qi Zhao; Xiaoyue Liu; Lina Ang; Haitong Zhe Sun; Wei Jie Seow (Environmental Pollution, 2026)

Using machine learning models to estimate ecotoxicity effect factors for various nanomaterials in life cycle assessment - Xiao Li; Yuan Yuan; Ang Li; Wei Sun; Weichun Ma (Journal of Hazardous Materials, 2026)

Coupled molybdenum and iron isotopes distinguish seawater and hydrothermal inputs to seep carbonates - Hangyu Nan; Xiaoming Miao; Hongxiang Guan; Ang Li; Zhilei Sun; Thomas J. Algeo; Davide Oppo; Nengyou Wu; Sanzhong Li (Geochimica et Cosmochimica Acta, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Research progress of cereals and their fermentation products in the prevention of metabolic dysfunction-associated steatotic liver disease - Chan Zhang; Yike Zhai; Arzugul Ablimit; Wenbo Liu; Duchen Zhai; Qing Sun; Lichao Dong; Chenran Yuchi; Ang Huang; Bobo Zhang; Chengjian Liu; Baoguo Sun; et al. (Food Bioscience, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Revealing thermoelectric property-performance correlations for the design of self-powered sensors - Zijian Lin; Bangzhou Tian; Xiaobo Tan; Chuke Zhao; Jiaxing Luo; Zhilong Zhao; Fan Feng; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2026)

Cognitive and emotional dysregulation in T-cell-deficient mice: the role of hippocampal neurogenesis and synaptic plasticity - Yongho Cho; Bokyung Jung; Sohee Jeong; Changjong Moon; Hae-June Lee; Mary Jasmin Cabillon Ang; Seung Pil Yun; Yeonghoon Son; Joong-sun Kim (Molecular & Cellular Toxicology, 2026)

Ecological risk and source apportionment of heavy metals in surface sediments from a key shellfish production area in Northern Liaodong Bay, China - Ang Li; Suyan Xue; Muzhan Sun; Qingbin Ma; Jiaqi Li; Lulei Liu; Ling Zhu; Yuze Mao (Marine Environmental Research, 2026)

Combining nontarget and target analysis to determine organic pollutants in secondary copper and aluminum smelter fly ash - Zeyin Peng; Dan Xia; Shuangshuang Zhao; Ang Zhao; Dongdong Zhang; Yuhao Sun; Yifei Sun (Journal of Environmental Sciences, 2026)

CFD Numerical Simulation Study on Hydrogen Fuel Combustion and Emission Characteristics of Marine Two-Stroke Low-Speed Engines - Zhizheng Wang; Hao Guo; Ang Sun; Song Zhou; Jialu Song; Yi Chai; Yue Chen (Journal of Marine Science and Engineering, 2026)
To meet the global climate change challenge and the International Maritime Organization’s (IMO) greenhouse gas emission reduction strategy, and promote the shipping industry’s transition to clean energy, this study focuses on the 6S35 2-stroke marine low-speed engine to explore hydrogen fuel combustion and emissions in the cylinder. A detailed chemical reaction kinetics model is constructed on the CONVERGE platform, coupling 42 components and 168 elementary reactions, integrating the SAGE combustion model with the extended Zeldovich NOx mechanism for refined numerical simulation of hydrogen combustion. Model validation shows the cylinder pressure peak simulation error is within 5%. Research results indicate hydrogen fuel has significant premixed combustion characteristics with a violent and concentrated heat release. Under simulation, the cylinder explosion pressure reaches about 28 MPa, and the max combustion temperature nears 3000 K, far exceeding traditional diesel engines. In terms of emissions, hydrogen’s carbon-free characteristic keeps CO2 and CO emissions at extremely low levels (concentrations of approximately 0.02 and 0.085, respectively); whereas NOx emissions exhibit strong “high temperature dependence” and “expansion cooling effect,” with peak concentrations approaching 0.00042. This numerical model can effectively predict the combustion performance of hydrogen fuel, potentially providing a reference for optimizing fuel injection strategies and combustion chamber design to achieve efficient and clean combustion, and offering a theoretical basis for the development and commercial application of marine hydrogen fuel engines.

An integrated meteorological adaptive simulation-optimization framework for real-time irrigation scheduling considering perfect weather forecasts - Kexin Li; Yanan Jiang; Ang Li; Xiangzhe Tian; Jiatong Lu; Tingting Wei; Jiangfeng Xiangli; Xifeng Huang; Yongmin Li; Shikun Sun (Agricultural Systems, 2026)

The CsWRKY3–CsHB7 transcriptional cascade promotes temperature-responsive peel pigmentation via CsCCD4b-mediated β-citraurin biosynthesis in citrus - Ranran Wei; Ang Fu; Yu Fang; Quan Sun; Zhijing Mo; Pengtao Yue; Ying Liang; Zongzhou Xie; Lijun Chai; Junli Ye; Xiuxin Deng (Molecular Plant, 2026)

ALM-LED: autonomous LiDAR mapping in underground space with Luojia explorer anti-collision drone - Shangzhe Sun; Chi Chen; Bisheng Yang; Yuhang Xu; Leyi Zhao; Yong He; Ang Jin; Liuchun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Synergistic lipid-lowering effects of Monascus purpureus and honeysuckle co-fermentation products: Insights from metabolomics, network pharmacology, and cellular experiments - Arzugul Ablimit; Qing Sun; Mengxue Chen; Huijun Dong; Wenbo Liu; Yike Zhai; Duchen Zhai; Ang Huang; Dingrong Kang; Baoguo Sun; Chengtao Wang; Chan Zhang (Food Bioscience, 2025)

Fully exposed Fe clusters activated with interfacial oxygen vacancy for accelerating catalytic ozonation of electron-deficient 1-adamantanecaboxylic acid through interfacial electronic metal-support interactions - Xuan Qu; Lu Wang; Zhi-Qiang Sun; Ang Li; Jun Ma (Chemical Engineering Journal, 2025)

Impact of Fluid Sloshing on BOG Generation in Type B LNG Tanks During Ship Emergency Stops - Haikang Zhao; Gang Wu; Jiachen Chen; Xigang Pu; Sicong Wang; Yuhao Yuan; Ang Sun (Journal of Marine Science and Engineering, 2025)
The safe and efficient transport of Liquefied Natural Gas (LNG) is critically dependent on understanding fluid dynamics within cargo tanks, which directly influence structural integrity and operational safety. Study employs the Volume of Fluid (VOF) method to simulate fluid sloshing and phase change dynamics in Type B LNG cargo tanks during emergency stop conditions. The transient simulations employ a time step of 5 × 10−3 s, a model with 46,840 grids, and the analysis focuses on impact forces on tank walls, their dependence on filling levels. Results show that the flow disturbance caused by vessel rolling increases BOG generation fluctuations by approximately 35%. Sloshing significantly increases BOG generation, particularly after a 10 s relaxation period, as the initial shock enhances heat transfer and mixing, accelerating vapor production. Original components of LNG are sensitive to BOG generation and impact forces on the front bulkhead are significantly higher than on the rear, with peak impacts occurring. The filling rate is a critical parameter influencing fluid dynamics and safety in LNG transportation. Impact magnitude increases with fill level up while at about 80% it declines; impact timing shortens at higher fill ratios. A BOG generation mechanism in which microscale turbulence and ongoing thermal imbalance govern the kinetics of evaporation phase transitions was proposed. It was discovered that the impact forces and BOG production exhibit rise–fall–rise patterns driven by impact dynamics, condensation, and evaporation processes. The findings highlight the critical role of fluid sloshing in affecting tank safety and operational efficiency, offering insights into designing more resilient LNG cargo tanks and optimizing transportation safety and economy.

Development and characterization of magnetic cellulose adsorbents functionalized with polyacrylic acid - Chengmin Hou; Zi'’ang Zhao; Fanglin Li; Yuan Bai; Chuangchuang Ren; Chenyu Li; Ze Fan; Wanting Jia; Ying Zhang; Weimin Yan; Yuru Li; Yiting Yang; et al. (Journal of Water Process Engineering, 2025)

Sand encased by fine-grained sediment regulates methane migration through the gas hydrate stability zone - Jiliang Wang; Ang Li; Wei Zhang; Jin Sun; Jiecheng Zhang; Xueqing Zhou; Shiguo Wu (Earth and Planetary Science Letters, 2025)

Supersaturation mechanisms and regulation strategies in nucleation-induced crystallization for high-purity fluoride recovery from photovoltaic wastewater - Zhihao Fu; Yadong Wang; Xuan Shi; Danheng Zhou; Zhilin Li; Pengkang Jin; Kunhao Li; Guohua Zhang; Ang Mei; Bingjie Sun; Yun Zhang (Chemical Engineering Journal, 2025)

Scale-factor-based regional zenith tropospheric delay modeling for real-time precise point positioning - Hao Chen; Ningbo Wang; Zishen Li; Kefei Zhang; Suqin Wu; Peng Sun; Ang Liu; Gongwei Xiao (Advances in Space Research, 2025)

Making Restoration Effective for Dynamic Coastal Wetlands - Qiang He; Zu'ang Li; Chris S. Elphick; Yizhou Sun; William J. Sutherland; Nigel G. Taylor; Kerstin Wasson (Global Change Biology, 2025)
To halt and reverse the trends of ecosystem loss and degradation under global change, nations globally are promoting ecosystem restoration. Restoration is particularly crucial to coastal wetlands (including tidal marshes, mangrove forests, and tidal flats), which are among the most important ecosystems on Earth but have been severely depleted and degraded. In this review, we explore the question of how to make restoration more effective for coastal wetlands in light of the often‐overlooked dynamic nature of these transitional ecosystems between land and ocean. Currently, restoration efforts have focused on removing anthropogenic threats, habitat reconstruction, and planting foundation species, often with mixed success and high costs. The challenges largely lie in the abiotic and biotic dynamics of these transitional ecosystems, including (i) fluctuating environmental stresses, (ii) variable trophic and nontrophic species interactions, (iii) changing connectivity with adjacent land, sea, and freshwater systems, and (iv) accelerating climate change, including sea level rise, droughts, and storms. Future restoration should explicitly account for these abiotic and biotic dynamics from threat removal to habitat reconstruction, assisted succession, and post‐restoration management. We highlight novel yet practical measures to enhance success. In the coming decades, bending the curve of coastal wetland loss and degradation globally also requires better understanding of the abiotic and biotic dynamics of these transitional ecosystems prone to change, using this understanding to develop innovative restoration approaches, and applying new approaches to upscale restoration in synergy with socioeconomic development. Critical to these efforts are collaborations among ecologists, policymakers, business investors, restoration practitioners, and the many millions of people dependent on coastal wetlands.

Nickel-doped ZIF-L as a high-performance catalyst for peroxymonosulfate activation and singlet oxygen-mediated As(III) removal - Jian Ye; Chuang Li; Zhiming Yang; Xuan Hu; Qiang Chen; Ang Sun; Mingyang Dai; Shaobo Liu; Chunping Yang (Journal of Environmental Chemical Engineering, 2025)

Variability of urinary metal in short-, mid-, long-term periods and its optimal sampling strategy: A novel epidemiological insight to exposure classification - Yanbing Li; Liu Liu; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Ming Yang; Lingli Sun; Ang Li; Qun Xu (Environmental Research, 2025)

The PpAHL17-PpHYH module is involved in light-independent anthocyanin accumulation in fruit peel of Prunus persica - Xiaoyu Zhang; Shihang Sun; Xin Liu; Junren Meng; Mingzhu Yuan; Ang Li; Wenyi Duan; Lei Pan; Zhiqiang Wang; Wenfang Zeng; Liang Niu (Plant Cell Reports, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

Investigation of the synergistic effects of reaction-diffusion processes in hierarchical macro-mesoporous electrodes of solid oxide fuel cells - Mingyuan Sun; Ang Li; Xuejie Zhang; Yuxuan Fei; Lei Zhu; Zhen Huang (Chemical Engineering Journal, 2025)

Peroxisomal biogenesis factor 11 as a novel target to trigger lipid biosynthesis and salt stress resistance in oleaginous Tetradesmus obliquus - Yunzhuan Xue; Wei Wang; Xiajule Sheng; Zexu Zheng; Zihan Wang; Fangling Ding; Jinjin Li; Zhiwei Sun; Yu’ang Cai; Xianhua Wang; Jiao Xue (Bioresource Technology, 2025)

Identification of elite alleles associated with glume-opening angle in rice natural population - Yingying Zhao; Hui Jiang; Chunyu Jing; Tianhu Li; Yanan Zhang; Zhengbo Liu; Yinping Chang; Mingyu Du; Hao Sun; Jinghan Sun; Yang Ang; Xianping Cheng; et al. (Euphytica, 2025)

Development of red grapefruit jam fermented with Monascus purpureus: Effect of naringenin on Monascus purpureus growth and metabolism - Chan Zhang; Congcong Wang; Arzugul Ablimit; Mengxue Chen; Qing Sun; Huijun Dong; Wenbo Liu; Ang Huang; Bobo Zhang; Wenlin Hu; Chengjian Liu; Chengtao Wang (Food Bioscience, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Polylactic acid microplastics induced negative priming and improved carbon sequestration via microbial processes in different paddy soils - Liying Chen; Lanfang Han; Fayuan Wang; Qi'ang Chen; Hongkai Huang; Jie Wang; Chuanxin Ma; Ke Sun; Matthias C. Rillig; Yakov Kuzyakov; Zhifeng Yang (Soil Biology and Biochemistry, 2025)

Effect of the LIF gene on the cell cycle and apoptosis of ovarian granulosa cells in white Muscovy ducks - Qing-hua Tao; Ning-ning Sun; Meng-shi Wang; Wan-xin Zhao; Wei Liu; Xu Zhang; Ang Li (Theriogenology, 2024)

A new strategy to design the purification process of ethyl tertiary butyl ether gasoline additive via hybrid extractive-reactive distillation - Zong Yang Kong; Shirui Sun; Tiffany Ang; Ao Yang; Hwai Chyuan Ong; Jaka Sunarso (Process Safety and Environmental Protection, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Large-scale oyster farming accelerates the removal of dissolved inorganic carbon from seawater in Sanggou Bay - Jiaqi Li; Zengjie Jiang; Meng Zhang; Xin Sun; Minghui Jiao; Jiamin Li; Suyan Xue; Ang Li; Longzhen Liu; Ling Zhu; Yuze Mao (Marine Environmental Research, 2024)

Synthesis of nitrogen-doped crystalline Ga2O3 thin films via trimethylgallium doped NH3/H2/N2/O2 premixed stagnation flames - Lun’ang Li; Shengfeng Luo; Mengzhao Chang; Guanjie Yin; Mingchen Sun; Jingrui Ma; Xiao Wei Sun; Igor Rahinov; Bo Zhou (Fuel, 2024)

Boosted photocatalytic H2O2 production in pure water with amino-modified N, S-doped carbon dots - Haoyuan Qin; Lei Sun; Suchang Zou; Ang Bian; Yanhua Cui; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

The MYB transcription factor PpMYB5 regulates Pp4CL1/Pp4CL2 expression to promote lignin biosynthesis of fruit russeting in the flat nectarine - Yule Miao; Wenyi Duan; Ang Li; Mingzhu Yuan; Junren Meng; Hongmei Wang; Lei Pan; Shihang Sun; Guochao Cui; Caiyun Shi; Liang Niu; Wenfang Zeng (Plant Cell Reports, 2024)

High valent manganese-oxo species activation of peroxymonosulfate by different phases manganese oxides nanoplates for catalytic water decontamination - Ang Li; Bin Li; Li-Ming Sun; Le-Xuan Liu; Chang Liu; Ya-Meng Dong; Xing Zhang (Chemical Engineering Journal, 2024)

Ultrafast hot electron transfer and trap-state mediated charge separation for boosted photothermal-assisted photocatalytic H2 evolution - Hao Yuan; Haoyuan Qin; Kaiqu Sun; Xinhai Sun; Jialin Lu; Ang Bian; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

Coral spawning patterns on the Luhuitou fringing reef in Hainan Island of the northern South China Sea - Youfang Sun; Yuyang Zhang; Lei Jiang; Xiaolei Yu; Lintao Huang; Tao Yuan; Jianhui Yang; Jiansheng Lian; Chengyue Liu; Put Ang; Hui Huang (Frontiers in Marine Science, 2024)
Observation of coral spawning times is valuable to detect spawning patterns and identify the potential mechanisms behind coral reproduction. Although large amount of data on global coral spawning records have become available over the past decades, information on coral spawning in the northern South China Sea remains scarce. In this study, we investigated the spawning patterns of scleractinian corals in Luhuitou fringing reef, Hainan Island, China, from 2009 to 2021 in relation to lunar cycles (month and day). The spawning times of 22 coral species from five genera ( Acropora , Montipora , Platygyra , Dipsastraea , and Galaxea ) within three families (Acroporidae, Merulinidae, and Euphylliidae) were recorded, with spawning occurring from lunar February to May 2009–2021. Recorded spawning events started at a period of increasing seawater temperature. Acropora , the most documented genus, spawned between lunar February and April, but primarily in lunar March. Importantly, the spawning time of Acropora was delayed for one lunar month in 2016 most likely due to a rapid decrease in monthly mean seawater temperature in lunar February. Spawning lunar days before, on or after full moon of corals in the Luhuitou Reef, including those of the Acropora species, were highly variable between years even for the same species. No predictable pattern of spawning times can thus be detected. Nonetheless, our results fill up an information gap on coral spawning patterns in the northern South China Sea that may be useful for further understanding of the reproductive biology of scleractinian corals throughout the Indo–West Pacific.

A neural m6A pathway regulates behavioral aggregation in migratory locusts - Xianliang Huang; Qing Li; Yanan Xu; Ang Li; Shanzheng Wang; Yusheng Chen; Chunrui Zhang; Xia Zhang; Hailin Wang; Cong Lv; Baofa Sun; Shaoqin Li; et al. (Science China Life Sciences, 2024)

Lateral migration of methane at a cold seep: Evidence from U–Th dating of methane-derived authigenic carbonate in the Middle Okinawa Trough - Ang Li; Nengyou Wu; Zhifeng Wan; Qing Li; Zhilei Sun; Feng Cai; Dong Feng (Marine and Petroleum Geology, 2024)

Enhancing physicochemical, antimicrobial, and release properties of fish skin gelatin films using dual-layer nanoparticles loaded with tea polyphenols/kojic acid for air-dried chicken preservation - Ang Zhang; Xiankang Fan; Xiaoqun Zeng; Jue Xu; Changyu Zhou; Qiang Xia; Yangying Sun; Zhen Wu; Daodong Pan (Food Hydrocolloids, 2024)

Design and fabrication of self-suspending aluminum-plastic/semiconductor photocatalyst devices for solar energy conversion - Zhi-Ang Zhao; Jingyun Mao; Chengjing Lu; Shuangqiao Yang; Qingrong Qian; Qinghua Chen; Hun Xue; Xiaoli Sun; Min-Quan Yang (Journal of Environmental Sciences, 2024)

Functionally separated electronic band engineering via multi-element doping plus high-density defects advances board-temperature-range thermoelectric performance in GeTe - Jianglong Zhu; Xiaobo Tan; Dong Pan; Yanni Luo; Ruiheng Li; Xuri Rao; Ruihuan Cheng; Chengliang Xia; Yue Chen; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Cooperation of carbon doping and carbon loading boosts photocatalytic activity by the optimum photo-induced electron trapping and interfacial charge transfer - Hao Yuan; Haoran Sun; Yuxing Shi; Jiaxuan Wang; Ang Bian; Youyou Hu; Feng Guo; Weilong Shi; Xin Du; Zhenhui Kang (Chemical Engineering Journal, 2023)

Intracellular electron competition in response to the oxygen pressure of the aerobic denitrification process in an O2-based membrane biofilm reactor (MBfR) for nitrate removal - Liang Feng; Fei-yun Sun; Jixian Yang; Di Cui; Zuo-hua Li; Shanshan Pi; He-Ping Zhao; Ang Li (Science of The Total Environment, 2023)

Effects of cascading reservoirs on streamflow and sediment load with machine learning reconstructed time series in the upper Yellow River basin - Junjian Fan; Guangju Zhao; Xingmin Mu; Ang Lu; Peng Tian; Peng Gao; Wenyi Sun (CATENA, 2023)

Effects of heat and hyposalinity on the gene expression in Acropora pruinosa larvae - Apple Pui Yi Chui; Yue Him Wong; Jin Sun; Taison Ka Tai Chang; Jian-Wen Qiu; Pei-Yuan Qian; Put Ang (Frontiers in Marine Science, 2023)
Introduction Climate change has resulted in elevated sea surface temperature as well as increased frequency of extreme weather events, e.g. cyclones and rainstorms, which could lead to reduced seawater salinity. While temperature effects on corals have been widely examined, the combined effects of both temperature and salinity on corals, especially their early stages, remain poorly known. This study aimed to examine how the larvae of Acropora pruinosa in a marginal coral habitat, Hong Kong, respond to high temperature (+5°C ambient, HT), low salinity (26 psu, LS), and the combined effects of both stressors (HTLS). Methods We recorded larval survival and settlement success under different experimental treatments, and used RNA-Seq technique to compare the gene expression patterns of these larvae to understand the underlying molecular mechanism of stress responses. Results Our results showed that the survivorship of coral larvae was not affected in all experimental treatments, with all larvae surviving through the 72-hour period of the experiment. Yet, larval settlement was compromised under all stress treatments. The settlement rates were 39.3%, 12%, and 0% for the elevated temperature, reduced salinity, and the combined treatment, respectively, which were all significantly lower than that under the control treatment (78%). We demonstrated that low salinity (LS) triggered responsive gene sets with functions in ATP production, protein translation, and receptor for neuroactive ligands. In addition, high temperature (HT) treatment also triggered MAPK and NF-kB signaling and apoptosis in these coral larvae. The combined stressor treatment (HTLS) acted synergistically, resulting in the up-regulation of intracellular transducers that could trigger the intrinsic apoptosis pathway. This may explain the total failure in larval settlement under HTLS that could further increase larval vulnerability in the natural environment. Discussion Our results provide new insights into the molecular responses of coral larvae and represent an essential first step in expanding ourunderstanding of the mechanisms of tolerance that may be exhibited by coral larvae exposed to multiple stressors.

A review of additives use in straw composting - Mingyue Piao; Ang Li; Huishi Du; Yuwei Sun; Hongxue Du; Honghui Teng (Environmental Science and Pollution Research, 2023)

Geographical distance, host evolutionary history and diet drive gut microbiome diversity of fish across the Yellow River - Baozhu Pan; Xu Han; Ke Yu; He Sun; Rong Mu; Chun‐Ang Lian (Molecular Ecology, 2023)
Fish represent a large part of the taxonomic diversity of vertebrates and are of high commercial value. However, the factors influencing the gut microbiota composition of freshwater fish over large spatial scales remain unclear. Therefore, this study explored gut microbiome diversity in 24 fish species from the Yellow River, which spans over 1500 km across China. The results showed that geographical distance, host phylogeny and diet significantly influenced gut microbial community diversity, whereas sex, body length and body weight had minimal influence. Geographical distance was the primary factor shaping gut microbiota, and dissimilarity in microbial community structure increased with an increase in geographical distance, which was mainly driven by dispersal limitation. The microbial communities were more homogeneous at higher host taxonomic resolutions due to the dominant role of homogeneous selection in community convergence. Phylosymbiosis was observed across all host species, with a stronger pattern in Cypriniformes, which harbour host‐specific microbial taxa. Host diet explained little variation in gut microbiome diversity, although it was significant for all diversity metrics tested. These findings collectively suggest that the geographical and host‐based patterns of fish gut microbiota tend to be shaped by different ecological forces across the Yellow River. The present work provides a robust assessment of multiple factors driving fish gut microbial community assembly and offers insight into the mechanisms underlying shifts in fish gut microbiota in rivers across large spatial scales.

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Characterization and shifting of microbial community to denitrification for anaerobic sulfamethoxazole biodegradation with different electron acceptors - Xiaoli Su; Feiyun Sun; Jianjun Zhang; Dingyu Xing; Xiaoying Li; Zi Song; Liang Feng; Zhichao Huang; Ang Li (Journal of Cleaner Production, 2023)

Low-temperature-resistance granulation of activated sludge and the microbial responses to the granular structural stabilization - Chunyan Yuan; Feiyun Sun; Jianjun Zhang; Liang Feng; Honghua Tu; Ang Li (Chemosphere, 2023)

Hsa_circ_0006732 regulates colorectal cancer cell proliferation, invasion and EMT by miR-127-5p/RAB3D axis - Tao Yang; Jufeng Sun; Wei Wang; Dongsheng Li; Xianxu Yang; Ang Jia; Yinda Ma; Zhongkai Fan (Molecular and Cellular Biochemistry, 2022)

Recent Progress in Modeling and Control of Bio-Inspired Fish Robots - Boai Sun; Weikun Li; Zhangyuan Wang; Yunpeng Zhu; Qu He; Xinyan Guan; Guangmin Dai; Dehan Yuan; Ang Li; Weicheng Cui; Dixia Fan (Journal of Marine Science and Engineering, 2022)
Compared with traditional underwater vehicles, bio-inspired fish robots have the advantages of high efficiency, high maneuverability, low noise, and minor fluid disturbance. Therefore, they have gained an increasing research interest, which has led to a great deal of remarkable progress theoretically and practically in recent years. In this review, we first highlight our enhanced scientific understanding of bio-inspired propulsion and sensing underwater and then present the research progress and performance characteristics of different bio-inspired robot fish, classified by the propulsion method. Like the natural fish species they imitate, different types of bionic fish have different morphological structures and distinctive hydrodynamic properties. In addition, we select two pioneering directions about soft robotic control and multi-phase robotics. The hybrid dynamic control of soft robotic systems combines the accuracy of model-based control and the efficiency of model-free control, and is considered the proper way to optimize the classical control model with the intersection of multiple machine learning algorithms. Multi-phase robots provide a broader scope of application compared to ordinary bionic robot fish, with the ability of operating in air or on land outside the fluid. By introducing recent progress in related fields, we summarize the advantages and challenges of soft robotic control and multi-phase robotics, guiding the further development of bionic aquatic robots.

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Research on Wetting Deformation Model of Coarse-Grained Materials of Earth-rock Dam - Hongyang Zhang; Pengju Han; Qin He; Yadong Sun; Ziyi Song; Zelin Ding; Ang Niu (Arabian Journal of Geosciences, 2022)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Regulation of glutamine synthetase activity by transcriptional and posttranslational modifications negatively influences ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Shuqi Song; Zehua Sun; Lingdan Lian; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Glutamine synthetase (GS), a central nitrogen metabolic enzyme, plays important roles in the nitrogen regulation network and secondary metabolism in fungi. However, the mechanisms by which external nitrogen sources regulate fungal GS activity have not been determined. Here, we found that GS activity was inhibited under nitrate conditions in Ganoderma lucidum . By constructing gs ‐silenced strains and adding 1 mM GS inhibitor to inhibit GS activity, we found that a decrease in GS activity led to a decrease in ganoderic acid biosynthesis. The transcription of gs increased approximately five fold under nitrate conditions compared with that under ammonia. Electrophoretic mobility shift and yeast one‐hybrid assay showed that gs was transcriptionally regulated by AreA. Although both gs expression and GS protein content increased under nitrate conditions, the GS activity still decreased. Treatment of recombinant GS with SIN‐1 (protein nitration donor) resulted in a strengthened nitration accompanied by a 71% decrease in recombinant GS activity. Furthermore, intracellular GS could be nitrated from mycelia cultivated under nitrate conditions. These results indicated that GS activity could be inhibited by NO‐mediated protein nitration. Our findings provide the first insight into the role of transcriptional and posttranslational regulation of GS activity in regulating secondary metabolism in fungi.

Inversion of Evaporation and Water Vapor Transport Using HY-2 Multi-Sensor Data - Dong’ang Liu; Jian Sun; Changlong Guan (Journal of Ocean University of China, 2020)

Dual functions of AreA, a GATA transcription factor, on influencing ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Zehua Sun; Dengke Shi; Shuqi Song; Lingdan Lian; Liang Shi; Ang Ren; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2019)
Summary Nitrogen metabolism repression (NMR) has been well studied in filamentous fungi, but the molecular mechanism of its effects on fungal secondary metabolism has been generally unexplored. Ganoderic acid (GA) biosynthesis in Ganoderma lucidum differs between ammonia and nitrate nitrogen sources. To explain the functions of NMR in secondary metabolism, AreA, which is a core transcription factor of NMR, was characterized in G . lucidum . The transcription level of AreA was dramatically increased (approximately 4.5‐folds), with the nitrate as the sole nitrogen source, compared with that with ammonia as the source. In addition, the expression of related genes involved in NMR was changed (upregulated of MeaB and downregulated of Nmr and GlnA ) when AreA was knockdown. Yeast one‐hybrid and electrophoretic mobility shift assay results showed that AreA could directly bind to the promoter of fps (encoding farnesyl‐diphosphate synthase) to activate its expression. However, GA biosynthesis was increased (27% in the ammonia source and 77% in the nitrate source) in AreAi mutant strains versus that in control strains. These results showed that another important factor must participate in regulating GA biosynthesis other than the direct activation of AreA. Furthermore, we found that the content of nitric oxide (NO) was increased approximately 2.7‐folds in the nitrate source compared with that in the ammonia. By adding the NO donor (SNP) or scavenger (cPTIO) and using NR ‐silenced or NR ‐overexpressed strains, we found that there was a negative correlation between the NO contents and GA biosynthesis. NO generated by nitrate reductase (NR) during the nitrogen utilization burst and could negatively influence GA biosynthesis. As a global transcription factor, AreA could also regulate the expression of NR . Our studies provide novel insight into the dual functions of AreA in GA biosynthesis during nitrogen assimilation.

Preparation of Deoxycholate-Modified Docetaxel-Cimetidine Complex Chitosan Nanoparticles to Improve Oral Bioavailability - Yingxin Xu; Tianxu Fang; Yifan Yang; Li’ang Sun; Qi Shen (AAPS PharmSciTech, 2019)

Influence of heterogeneity on mechanical and acoustic emission behaviours of stratified rock specimens - Ang Li; Guo-jian Shao; Jing-bo Su; Yang Sun; Tian-tang Yu; Hou-gai Shi (European Journal of Environmental and Civil Engineering, 2018)

Safety, pharmacokinetics, and pharmacodynamics of BMS-986142, a novel reversible BTK inhibitor, in healthy participants - Sun Ku Lee; Jun Xing; Ian M. Catlett; Robert Adamczyk; Amber Griffies; Ang Liu; Bindu Murthy; Miroslawa Nowak (European Journal of Clinical Pharmacology, 2017)

Transgenerational Inheritance of Paternal Neurobehavioral Phenotypes: Stress, Addiction, Ageing and Metabolism - Ti-Fei Yuan; Ang Li; Xin Sun; Huan Ouyang; Carlos Campos; Nuno B. F. Rocha; Oscar Arias-Carrión; Sergio Machado; Gonglin Hou; Kwok Fai So (Molecular Neurobiology, 2016)

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

Removal of Phenol Using Sulphate Radicals Activated by Natural Zeolite-Supported Cobalt Catalysts - Syaifullah Muhammad; Edy Saputra; Hongqi Sun; H. M. Ang; Moses O. Tadé; Shaobin Wang (Water, Air, & Soil Pollution, 2013)

Characterization of a compound bioflocculant produced by mixed culture of Rhizobium radiobacter F2 and Bacillus sphaeicus F6 - Lili Wang; Fang Ma; Yuanyuan Qu; Dezhi Sun; Ang Li; Jingbo Guo; Bing Yu (World Journal of Microbiology and Biotechnology, 2011)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)